Management and Follow-Up Practices of Women With Recurrent Stress Urinary Incontinence Following Transobturator Mid-urethral Synthetic Sling Procedure: A 6-Year Retrospective Monocentric University-Based Study - Huang, Yi; Chen, Zhengsen; Shen, Baixin; Shao, Yunpeng; Gao, Jie; Zhou, Yiduo; Margit, Fisch; Wei, Zhongqing; Ding, Liucheng (Frontiers in Surgery, 2021)
Purpose: The purpose of this study is to evaluate the efficacy of management and follow-up practices in repeat retropubic mid-urethral synthetic sling (MUS) procedure after transobturator tape/tension-free vaginal tape-obturator (TOT/TVT-O) failure, and to clarify the possible etiology of recurrent stress urinary incontinence. Methods: The charts of all women patients who underwent tension-free vaginal tape (TVT) slings after previous failed transobturator MUS procedures between February 2012 and November 2018 at a single center were reviewed retrospectively. The transperineal ultrasound was performed to assess the pre-operative or post-operative urethral mobility and location of the slings. Furthermore, some essential evaluations were also made, mainly including medical history, physical examination, 1 h pad test, and urodynamic study. Finally, primary outcomes were evaluated according to the above items at 3, 6, and 12 months after the second operation, respectively. Results: Thirty-five patients were included in the primary transobturator MUS sling procedure. At the 6 months follow-up, 32 (91.42%) patients were socially continent and negative in 1 h pad test. The transperineal ultrasound measurement results revealed that the bladder neck descent (BND) values were significantly decreased after the repeat sling operation, and better urinary continence function was observed according to the post-operative urodynamic study. Multifactorial etiologies resulted in recurrent stress urinary incontinence (SUI), including poor surgical technique, inadequate sling tension when treating ISD, and inappropriate sling position. Then the detail of the surgical procedure varied with the results of pre-operative evaluations, affecting the validity of the second sling. Conclusion: Recurrent SUI has resulted from multi factors, pre-operative urodynamic study and transperineal ultrasound might be valuable tools to guide repeat sling operation and predict post-operative outcomes. A repeat TVT procedure may be regarded as a remedial measure for a failed transobturator MUS operation.